Knockdown of angiopoietin-like 2 mimics the benefits of intermittent fasting on insulin responsiveness and weight loss. Issue 1 (January 2018) - Martel, Cécile; Pinçon, Anthony; Bélanger, Alexandre Maxime; Luo, Xiaoyan; Gillis, Marc-Antoine; de Montgolfier, Olivia; Thorin-Trescases, Nathalie; Thorin, Éric
Angiopoietin-like 2 (ANGPTL2) is an inflammatory adipokine linking obesity to insulin resistance. Intermittent fasting, on the other hand, is a lifestyle intervention able to prevent obesity and diabetes but difficult to implement and maintain. Our objectives were to characterize a link between ANGPTL2 and intermittent fasting and to investigate whether the knockdown of ANGPTL2 reproduces the benefits of intermittent fasting on weight gain and insulin responsiveness in knockdown and wild-type littermates mice. Intermittent fasting, access to food ad libitum once every other day, was initiated at the age of three months and maintained for four months. Intermittent fasting decreased by 63% (p < 0.05) gene expression of angptl2 in adipose tissue of wild-type mice. As expected, intermittent fasting improved insulin sensitivity (p < 0.05) and limited weight gain (p < 0.05) in wild-type mice. Knockdown mice fed ad libitum, however, were comparable to wild-type mice following the intermittent fasting regimen: insulin sensitivity and weight gain were identical, while intermittent fasting had no additional impact on these parameters in knockdown mice. Energy intake was similar between both wild-type fed intermittent fasting and ANGPTL2 knockdown mice fed ad libitum, suggesting that intermittent fasting and knockdown of ANGPTL2 equally lower feeding efficiency. These results suggest that the reduction of ANGPTL2 could be a useful and promising strategy to prevent obesity and insulin resistance, although further investigation of the mechanisms linking ANGPTL2 and intermittent fasting is warranted. Impact statement: Intermittent fasting is an efficient diet pattern to prevent weight gain and improve insulin sensitivity. It is, however, a difficult regimen to follow and compliance is expected to be very low. In this work, we demonstrate that knockdown of ANGPTL2 in mice fed ad libitum mimics the beneficial effects of intermittent fasting on weight gain and insulin sensitivity in wild-type mice. ANGPTL2 is a cytokine positively associated with fat mass in humans, which inactivation in mice improves resistance to a high-fat metabolic challenge. This study provides a novel pathway by which IF acts to limit obesity despite equivalent energy intake. The development of a pharmacological ANGPTL2 antagonist could provide an efficient tool to reduce the burden of obesity.